2006
DOI: 10.1080/01676830500505608
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Orbital Inflammatory Pseudotumor in Chinese Children

Abstract: Pediatric IOIP accounted for 11.5% of all IOIP patients. Pediatric cases had more sign of ptosis and less sign of proptosis than in adult IOIP. The full recovery response rate was low in children with IOIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 8 publications
2
52
0
11
Order By: Relevance
“…Ayrıca çocuklarda papil ödem ve iritis ile de karşılaşılabilmektedir. Orbital miyozit çocuklarda en sık görülen oftalmolojik belirtiler; oküler hareket kısıtlılığı, gözde ağrı, göz kapaklarında ödem, propitozis, yüksek orbital basınç, diplopi, konjonktival enjeksiyon şeklinde karşımıza çıkabilir (2,5). Ani başlayan ağrı orbital miyozitde karakteristik olarak daha sık görülür.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Ayrıca çocuklarda papil ödem ve iritis ile de karşılaşılabilmektedir. Orbital miyozit çocuklarda en sık görülen oftalmolojik belirtiler; oküler hareket kısıtlılığı, gözde ağrı, göz kapaklarında ödem, propitozis, yüksek orbital basınç, diplopi, konjonktival enjeksiyon şeklinde karşımıza çıkabilir (2,5). Ani başlayan ağrı orbital miyozitde karakteristik olarak daha sık görülür.…”
Section: Discussionunclassified
“…Üç aylık takip süresince hastalık tekrarlanmadı. rezolüsyon gösteren bir hastalıktır (5). NSOİ dakriyoadenit, perinörit, perisklerit gibi tipleri olsada idiyopatik orbital miyozit en sık görülen tipidir.…”
Section: Olgu Sunumuunclassified
See 1 more Smart Citation
“…Currently, there exists no previous report of inflammatory pseudotumor involving both the orbit and eye of which we are aware. Medical records of 209 IOIP cases at the Zhongshan Ophthalmic Center of Sun Yet-sen University, China, were reviewed between the periods of Jan 1,1978 and Dec 31,1999 with no patient demonstrating both orbital and eye involvement [8,9]. With regard to an IOIP involving both the orbit and eye, our cases were particularly unique in that we found that the lateral rectus muscle and temporal sclera of the right eye were severely affected.…”
Section: Discussionmentioning
confidence: 99%
“…streptococcal pharyngitis (Alshaikh et al, 2008;Belanger et al, 2010) and presumed allergic responses (Yan et al, 2006). There are cases of orbital myositis that develop after pregnancy (Hiraga et al, 2008;Mombaerts & Koornneef, 1997) and cases with a familial history (Jacob et al, 2007;Maurer & Zierz, 1999).…”
mentioning
confidence: 99%